ANALISIS HUBUNGAN KERJASAMA TIM UNTUK MENINGKATKAN EFISIENSI KERJA PADA PT MITHA SAMUDERA WIJAYA MEDAN - DINA ROLANNA SIMANUNGKALIT; lucy anna (Jurnal Media Informasi Manajemen, 2013)
This research aimed to analyze the relationship of Teamwork to Increase Work Efficiency in PT Mitha Samudera Wijaya Medan. This research method uses descriptive analysis and Pearson Correlation Method. In this research, the population is an employee at PT Mitha Samudera Wijaya Medan. Cencus method is used in this research in which consists of 42 employees at PT Mitha Samudera Wijaya Belawan. The result of this research indicate that there is a positive and significant relationship between Teamwork with Work Efficiency. Key Words :Teamwork and Work Efficiency